Budgetary Slack Memediasi Pengaruh Komitmen Organisasi Dan Kejelasan Sasaran Anggaran Terhadap Kinerja Manajerial - Pradita, Sharfina; Susilowati, Endah (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
The purpose of this study is to test and prove: The effect of organizational commitment on budgetary slack, The effect of budget goal clarity on budgetary slack, The effect of organizational commitment on managerial performance, The effect of budget goal clarity on managerial performance, The effect of budgetary slack on managerial performance, The effect of organizational commitment on managerial performance through budgetary slack, and The effect of budget goal clarity on managerial performance through budgetary slack. The method used is quantitative with the type of causality research. The method of determining the sample using purposive sampling. The analysis technique used in this research is PLS (Partial Least Squares). The results of this study are Organizational commitment has a significant positive effect on budgetary slack, Budget goal clarity has a insignificant positive effect on budgetary slack, Organizational commitment has a significant positive effect on managerial performance, Budget goal clarity has a negative insignificant negative effect on managerial performance, Budgetary slack has a significant positive effect on managerial performance, Organizational commitment has a significant positive effect on managerial performance through budgetary slack, and Budget goal clarity has a insignificant positive effect on managerial performance through budgetary slack.Â